2004
DOI: 10.1002/ps.908
|View full text |Cite
|
Sign up to set email alerts
|

Systemic activity of simeconazole and its derivatives in plants

Abstract: The systemic activity of simeconazole (RS-2-(4-fluorophenyl)-1-(1H-1,2,4-triazol-1-yl)-3-trimethylsilylpropan-2-ol) and a number of its derivatives in plants has been investigated to establish which portion of the structure of the molecule contributes to this outstanding activity. The results revealed that the hydroxyl group of the simeconazole moiety is essential for vapour-phase activity and translocation from roots of the compound. They showed that the presence of a fluorine atom in the structure was not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…For related literature, see: Chai et al (2003); Er-Rahimini & Mornet (1992); Ichikawa et al (2001); Jenkins et al (1989); Kim et al (2003); Nakib et al (1994); Sancak et al (2005); Tsuda et al (2004); Ueda (2003); Zhu et al (2000); Ç oruh et al (2003).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For related literature, see: Chai et al (2003); Er-Rahimini & Mornet (1992); Ichikawa et al (2001); Jenkins et al (1989); Kim et al (2003); Nakib et al (1994); Sancak et al (2005); Tsuda et al (2004); Ueda (2003); Zhu et al (2000); Ç oruh et al (2003).…”
Section: Related Literaturementioning
confidence: 99%
“…In a continuing search for pharmacologically active, 1,2,4-triazol and 1,2,4-triazol-5-one compounds, it has been found that most azole fungicides have been developed for diseases of cereal crops; examples include fluconazole (Ichikawa et al, 2001), ravuconazole (Ueda, 2003) and posaconazole . Moreover, 1,2,4-triazole derivatives have broad-spectrum biological effects, such as insecticidal (Tsuda et al, 2004), herbicidal (Chai et al, 2003), anticonvulsant (Er-Rahimini & Mornet, 1992), antitumor (Nakib et al, 1994) and plant growth regulatory activities (Jenkins et al, 1989).…”
Section: Commentmentioning
confidence: 99%
“…Triazole ring systems are typical planar 6-electron partially aromatic systems, and 1,2,4-triazole and its derivatives are used as starting materials for the synthesis of many heterocycles (Desenko, 1995). Recently, much attention has been focused on 1,2,4-triazole derivatives for their broadspectrum activities, such as fungicidal, insecticidal, herbicidal, anticonvulsant, antitumour and plant growth regulatory activities (Jenkins et al, 1989;Er-Rahimini & Mornet, 1992;Nakib et al, 1994;Chai et al, 2003;Tsuda et al, 2004).…”
Section: Commentmentioning
confidence: 99%
“…Recently, much attention has been focused on 1,2,4-triazole derivatives for their broad-spectrum fungicidal, insecticidal, herbicidal, anticonvulsant, antitumour and plant growth regulatory activities (Tsuda & Itoh, 2004;Chai et al, 2003;Er-Rahimini & Mornet, 1992;Nakib et al, 1994;Jenkins et al, 1989). Disubstituted 1,2,4-triazole derivatives have also been reported to show antituberculotic activities (I Â kizler et al, 1998).…”
Section: Commentmentioning
confidence: 99%